FINANCIAL LITERACY AND LOCUS OF CONTROL ON THE FINANCIAL BEHAVIOR OF THE K-POP FAN COMMUNITY IN MEDAN CITY - Nurwadiyah Nasution; Nurlaila; Tuti Anggraini (Pena Cendekia Insani, 2025)
This study aims to analyze the influence of financial literacy and locus of control on financial behavior within the K-pop fan community in Medan City. The background of this research is based on the phenomenon of consumptive lifestyles among K-pop fans, most of whom come from the younger generation. This study employs a quantitative approach using a survey method with 96 respondents who are members of the K-pop community in Medan. Data analysis was conducted using multiple linear regression tests with the assistance of SPSS 25 software. The results of the study show that, partially, financial literacy has a significant influence on financial behavior (0.000 < 0.05), while locus of control does not have a significant influence on financial behavior (0.724 > 0.05). However, through simultaneous testing (F-test), it was found that financial literacy and locus of control together have a significant influence on financial behavior (0.000 < 0.05). These findings highlight the importance of improving financial literacy among the younger generation to encourage healthy financial behavior, particularly within communities with consumptive tendencies. Therefore, community-based financial education becomes an important strategy in facing the demographic bonus era